Efficacy and safety of tafamidis doses in the Tafamidis in Transthyretin Cardiomyopathy Clinical Trial (ATTR‐ACT) and long‐term extension study. (12th November 2020) - Damy, Thibaud; Garcia‐Pavia, Pablo; Hanna, Mazen; Judge, Daniel P.; Merlini, Giampaolo; Gundapaneni, Balarama; Patterson, Terrell A.; Riley, Steven; Schwartz, Jeffrey H.; Sultan, Marla B.; Witteles, Ronald
Abstract : Aims: Tafamidis is an effective treatment for transthyretin amyloid cardiomyopathy (ATTR‐CM) in the Tafamidis in Transthyretin Cardiomyopathy Clinical Trial (ATTR‐ACT). While ATTR‐ACT was not designed for a dose‐specific assessment, further analysis from ATTR‐ACT and its long‐term extension study (LTE) can guide determination of the optimal dose. Methods and results: In ATTR‐ACT, patients were randomized (2:1:2) to tafamidis 80 mg, 20 mg, or placebo for 30 months. Patients completing ATTR‐ACT could enrol in the LTE (with placebo‐treated patients randomized to tafamidis 80 or 20 mg; 2:1) and all patients were subsequently switched to high‐dose tafamidis. All‐cause mortality was assessed in ATTR‐ACT combined with the LTE (median follow‐up 51 months). In ATTR‐ACT, the combination of all‐cause mortality and cardiovascular‐related hospitalizations over 30 months was significantly reduced with tafamidis 80 mg ( P  = 0.0030) and 20 mg ( P  = 0.0048) vs. placebo. All‐cause mortality vs. placebo was reduced with tafamidis 80 mg [Cox hazards model (95% confidence interval): 0.690 (0.487–0.979), P  = 0.0378] and 20 mg [0.715 (0.450–1.137), P  = 0.1564]. The mean (standard error) change in N‐terminal pro‐B‐type natriuretic peptide from baseline to Month 30 was −1170.51 (587.31) ( P  = 0.0468) with tafamidis 80 vs. 20 mg. In ATTR‐ACT combined with the LTE there was a significantly greater survival benefit with tafamidis 80 vs. 20 mg [0.700 (0.501–0.979), P  = 0.0374]. Incidence of adverse events in both tafamidis doses were comparable to placebo. Conclusion: Tafamidis, both 80 and 20 mg, effectively reduced mortality and cardiovascular‐related hospitalizations in patients with ATTR‐CM. The longer‐term survival data and the lack of dose‐related safety concerns support tafamidis 80 mg as the optimal dose. Clinical Trial Registration: ClinicalTrials.gov NCT01994889; NCT02791230. Abstract : Design of ATTR‐ACT and the LTE and reduction in all‐cause mortality with tafamidis 80 mg/61 mg compared with tafamidis 20 mg